2009
DOI: 10.1021/pr8010827
|View full text |Cite
|
Sign up to set email alerts
|

Entering a New Era of Rational Biomarker Discovery for Early Detection of Melanoma Metastases: Secretome Analysis of Associated Stroma Cells

Abstract: Metastasis in melanoma is associated with poor prognosis. Early detection may thus substantially improve patient survival. Here we present a novel biomarker discovery strategy based on proteome profiling and secretome analysis of primary cells. Tumor associated stroma cells secrete proteins that may act as powerful tumor promoters. This cell cooperativity is reversible and may thus be directly accessible to therapeutic intervention. The onset of these characteristic events seems to precede tumor progression. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 40 publications
2
44
0
Order By: Relevance
“…10 The cancer secretome has also been studied in different cancers including pancreatic, 11 nasopharyngeal, 12 thyroid, 13 lung adenocarcinoma, 14 oral, 15 ovarian, 16 colorectal, 17 breast 18 and melanoma. 19 A limited number of studies have been carried out in ESCC, wherein researchers have identified a small number of differentially expressed proteins. [20][21][22][23][24] A brief summary of studies carried out thus far is provided in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…10 The cancer secretome has also been studied in different cancers including pancreatic, 11 nasopharyngeal, 12 thyroid, 13 lung adenocarcinoma, 14 oral, 15 ovarian, 16 colorectal, 17 breast 18 and melanoma. 19 A limited number of studies have been carried out in ESCC, wherein researchers have identified a small number of differentially expressed proteins. [20][21][22][23][24] A brief summary of studies carried out thus far is provided in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…As every pathology-associated cell aberration will be associated with accompanying aberrations in protein expression, the responsible cells may be the perfect targets for discovery of potential biomarkers. We suggest that complex tissue proteome profiles can be better interpreted by referring to previously analyzed profiles of cells [26]. Based on multiple references of the most predominant tissue constituents, the data are pre-sorted according to biological criteria.…”
Section: Introductionmentioning
confidence: 99%
“…We have established proteome reference profiles of human fibroblasts, keratinocytes, the major blood constituents of dendritic cells (DCs) and endothelial cells at functional distinct states as well as primary and cultured hepatocytes [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…To search for biomarkers useful for the diagnosis of metastases, primary and metastatic cell lines were compared and several candidate biomarkers were successfully discovered (Table 4) (Bernard et al, 2003;Zuidervaart et al, 2006;Al-Ghoul et al, 2008). Proteomics analysis of melanoma-associated fibroblast stromal cells revealed the aberrant expression of several proteins not detected in normal fibroblasts (Paulitschke et al, 2009). These proteins may promote tumor progression.…”
Section: Screening For Tumor Tissues and Cell Linesmentioning
confidence: 99%
“…Table 5 summarizes a number of different reports in which comprehensive screening of biomarkers from serum and the secretome occurred. By comparing the secretome between melanoma and normal melanocyte, several potential biomarkers were successfully discovered (Pardo et al, 2007;Paulitschke et al, 2009). The traditional serological biomarkers of melanoma such as LDH, S100B and CRP lack sensitivity as early stage melanoma biomarkers.…”
Section: Screening Biomarkers Obtained From Serum and Secreted From Cmentioning
confidence: 99%